2006
DOI: 10.1002/path.2032
|View full text |Cite
|
Sign up to set email alerts
|

Epstein–Barr virus in breast cancer: artefact or aetiological agent?

Abstract: The Epstein-Barr virus (EBV) has been reported to be associated with a variety of different tumours; for some of these malignancies, including breast cancer, the association remains controversial. This might be due in part to differences in the methodologies used to detect EBV in tissue samples. One approach favoured by many groups is to use immunohistochemistry to detect an EBV protein, EBNA1, which is essential for the maintenance of viral latency in infected cells and therefore should be a good marker for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Whereas EBV infection in certain tumour types has been firmly established by several independent research groups, its association with other tumour entities is still controversial 27 56…”
Section: Controversiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas EBV infection in certain tumour types has been firmly established by several independent research groups, its association with other tumour entities is still controversial 27 56…”
Section: Controversiesmentioning
confidence: 99%
“…Studies assessing EBV association with breast adenocarcinomas have reported contradictory results 56. This is probably at least partly related to the antibody directed against EBNA1 (clone 2B4).…”
Section: Controversiesmentioning
confidence: 99%
“…Each of these viruses has known oncogenic potential and has been identified in normal and malignant human breast tissues. However, the identification of HPV, MMTV and EBV in breast tumours has been challenged [3][5]. The reasons for these challenges vary and include failure of some investigators to identify viral sequences in breast tumours and breast cancer cultured cell lines, concern about contamination of analyses based on polymerase chain reaction (PCR) techniques, and concern that outcomes based on immunohistochemistry may be non-specific and due to cross reacting proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Others found that the higher expression of EBV was present in the medullary than the lobular carcinoma. [34] EBV tends to infect young persons of both sexes suggesting a genetic predisposition or early life exposure. It also affects older ages if the immune system is diminished.…”
Section: Published By Sciedu Pressmentioning
confidence: 99%